The Effect of Religious Coping and Optimism on Psychological Well-Being among the Final-Year Undergraduate Students - Eko Sujadi (Indonesian Journal of Counseling and Development, 2021)
Psychological well-being (PWB) is a desirable condition for college students as it enhances the quality of their studies. Conversely, low psychological well-being can impede their learning process. This study aims to analyze the effect of religious coping and optimism on PWB, and the combined effect of religious coping and optimism on PWB. We employed a cross-sectional study design, and 202 final year students participated by completing the Psychological Wellbeing Scale, The Brief RCOPE, and the Life Orientation Test - Revised (LOT-R). Multiple regression analysis was used to test the hypotheses. The study found that religious coping and optimism have a partial effect on psychological well-being. Furthermore, the combined analysis yielded significant results. These findings have implications regarding the importance of attention to final year students. College/university administrators need to formulate prevention and intervention programs for students with impaired psychological well-being. Moreover, counseling services provided by professional counselors need to be maximized.